Ebola haemorrhagic fever in Africa: a necessary highlight - Samuel Adu-Gyamfi (Intelektual Pustaka Media Utama, 2019)
The purpose of this commentary is to re-evaluate the historic and scientific facts on Ebola haemorrhagic fever and the role of the international community, especially Economic Community of West African States (ECOWAS) in stemming the tide. It rehashes the argument on causes and prevention and draws attention of readers to emphasize the need for establishment of airport, sea port and border health posts with well drilled and efficient health professionals to be able to test, detect and quarantine persons with Ebola and treat them to prevent the spread of the disease from infected persons to primary or first contacts and secondary contacts. Significantly, countries in the West African sub-region are alarmed by the potential spread of the disease to countries that have hitherto been free of the disease. The potential global threat of the disease has been analysed and measures to be taken by countries within the West-African sub-region have been emphasized. This notwithstanding, does the declaration of countries as Ebola-free suggest the last of it?